Repetition in Walt Whitman’s “A Passage to India” - Matevosyan, Armine; Melkonyan, Anna (Armenian Folia Anglistika, 2010)
The article investigates the stylistic device of repetition which plays an underlying role in Whitman’s poetry. It brings rhythm and harmony to the poetry and helps convey higher moral values – wisdom, morality, various human states of mind and moods. Repetition with its various manifestations is a unique feature in Whitman’s poetry and it is impossible to imagine the great poet without his grand individual language. Undoubtedly, his poetry is the height of the art of repetition.